Análise dos argumentos das Diretrizes Curriculares da Educação Básica do Estado do Paraná no ensino de ciências nas séries finais do ensino fundamental - Oliveira, Rosineide de Jesus (2009)
The objective of this study is to analyze the process of formulation and implementation of the State Curriculum Guidelines - DCE, and the Science Teaching State Curriculum Guidelines - DCC in opposition to PCN in the state of Paraná. To accomplish the investigation the methodological procedures were: analysis of official and preliminary documents of Curriculum Guidelines of Paraná state; interviews with three groups of teachers: curriculum guidelines manufacturers or synthesizers, SEED, teachers of GP (Permanent Group) and teachers of basic education who received instructions to work effectively in classroom. The data were examined by Analysis of Content proposed by Laurence Bardin (1997). The results of our research showed that the DCC and the DCE keep, in general terms, two theoretical frameworks: the political, defined by choice of marxism to affirm the social dimensions that exist in a society of classes and to oppose the neoliberal view SEED says existing in PCN. The second point is related to the pedagogical concept that supports learning, Vygostsky theory and Ausubel Cognitivist theory for significant learning. In the specific plan, the Curriculum Guidelines provide methodological ways which start from main contents as principal route of access to scientific knowledge in opposition to pedagogy of projects and transversality of topics suggested in PCN. These issues, according to SEED, make scientific knowlege of a minor importance.